I am Martin Luther King, Jr. - Meltzer, Brad; Eliopoulos, Chris (New York, NY : Dial Books for Young Readers, an imprint of Penguin Random House, 2016)
"A biography of Martin Luther King Jr. that tells the story of how he used nonviolence to lead the civil rights movement"--
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; African Americans -- Biography; Juvenile literature; Civil rights workers -- United States; Biography; Juvenile literature; African Americans -- Civil rights; History -- 20th century; Juvenile literature; Civil rights movements -- United States; History -- 20th century; Juvenile literature; Nonviolence. -- United States; History -- 20th century; Juvenile literature; JUVENILE NONFICTION / Biography & Autobiography / Social Activists; JUVENILE NONFICTION / History / United States / 20th Century; JUVENILE NONFICTION / People & Places / United States / African American